Bifunctional Small Molecules Enhance Neutrophil Activities Against Aspergillus fumigatus in vivo and in vitro - Jones, Caroline N.; Ellett, Felix; Robertson, Anne L.; Forrest, Kevin M.; Judice, Kevin; Balkovec, James M.; Springer, Martin; Markmann, James F.; Vyas, Jatin M.; Warren, H. Shaw; Irimia, Daniel (Frontiers in Immunology, 2019)
Aspergillosis is difficult to treat and carries a high mortality rate in immunocompromised patients. Neutrophils play a critical role in control of infection but may be diminished in number and function during immunosuppressive therapies. Here, we measure the effect of three bifunctional small molecules that target Aspergillus fumigatus and prime neutrophils to generate a more effective response against the pathogen. The molecules combine two moieties joined by a chemical linker: a targeting moiety (TM) that binds to the surface of the microbial target, and an effector moiety (EM) that interacts with chemoattractant receptors on human neutrophils. We report that the bifunctional compounds enhance the interactions between primary human neutrophils and A. fumigatus in vitro, using three microfluidic assay platforms. The bifunctional compounds significantly enhance the recruitment of neutrophils, increase hyphae killing by neutrophils in a uniform concentration of drug, and decrease hyphal tip growth velocity in the presence of neutrophils compared to the antifungal targeting moiety alone. We validated that the bifunctional compounds are also effective in vivo, using a zebrafish infection model with neutrophils expressing the appropriate EM receptor. We measured significantly increased phagocytosis of A. fumigatus conidia by neutrophils expressing the EM receptor in the presence of the compounds compared to receptor-negative cells. Finally, we demonstrate that treatment with our lead compound significantly improved the antifungal activity of neutrophils from immunosuppressed patients ex vivo. This type of bifunctional compounds strategy may be utilized to redirect the immune system to destroy fungal, bacterial, and viral pathogens.